1998
DOI: 10.1021/jf970964i
|View full text |Cite
|
Sign up to set email alerts
|

Cotylenins and Fusicoccins Stimulate Seed Germination of Striga hermonthica (Del.) Benth and Orobanche minor Smith

Abstract: Several fungal metabolites were examined for their effects on germination of the root parasitic weeds witchweed, Striga hermonthica (Del.) Benth, and clover broomrape, Orobanche minor Smith. Among these metabolites cotylenins (CNs) and fusicoccins (FCs) at concentrations as low as 10-5 M induced high seed germination (>50%) of both parasites. Inhibitors of ethylene biosynthesis [2-(2-aminoethoxyvinyl)glycine (AVG)] and action [silver thiosulfate (STS)] reduced CN- and FC-induced Striga germination but not that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 36 publications
2
36
3
Order By: Relevance
“…Strigolactones, such as strigol (Cook et al 1966), sorgolactone , alectrol ) and orobanchol (Yokota et al 1998) are known as major seed germination stimulants exuded from host and non-host plant roots. In addition, dihydrosorgoleone, which was isolated from the hydrophobic exudates of sorghum roots (Chang et al 1986), jasmonic acid (Yoneyama et al 1998a), cotylenin and fusicoccin (Yoneyama et al 1998b) have been demonstrated to induce seed germination. The germination stimulants elicit ethylene biosynthesis in Striga seeds, which is essential to initiate seed germination (Logan and Stewart 1991;Yoneyama et al 1998b;Sugimoto et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strigolactones, such as strigol (Cook et al 1966), sorgolactone , alectrol ) and orobanchol (Yokota et al 1998) are known as major seed germination stimulants exuded from host and non-host plant roots. In addition, dihydrosorgoleone, which was isolated from the hydrophobic exudates of sorghum roots (Chang et al 1986), jasmonic acid (Yoneyama et al 1998a), cotylenin and fusicoccin (Yoneyama et al 1998b) have been demonstrated to induce seed germination. The germination stimulants elicit ethylene biosynthesis in Striga seeds, which is essential to initiate seed germination (Logan and Stewart 1991;Yoneyama et al 1998b;Sugimoto et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dihydrosorgoleone, which was isolated from the hydrophobic exudates of sorghum roots (Chang et al 1986), jasmonic acid (Yoneyama et al 1998a), cotylenin and fusicoccin (Yoneyama et al 1998b) have been demonstrated to induce seed germination. The germination stimulants elicit ethylene biosynthesis in Striga seeds, which is essential to initiate seed germination (Logan and Stewart 1991;Yoneyama et al 1998b;Sugimoto et al 2003). Moreover, the conditioning with fluridone induced the formation of haustoriumlike structures in S. asiatica seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much attention has been focused on the isolation and identification of novel metabolites including those isolated from plant root exudates and fungal metabolite. The fungal metabolite cotylenins and fusicoccins have been reported to induce over 50% seed germination of O. minor even at very low concentrations (Yoneyama et al, 1998). Germination stimulants, both natural and synthetic, have good potential as effective tools of management of broomrape, but much remains to be learned about their structure, activity, and stability in the soil.…”
Section: Germination Stimulantsmentioning
confidence: 99%
“…As a matter of fact, an experiment designed to separate seeds and mycelia physically with a cellophane film demonstrated that certain diffusible chemical(s) serve as signals for the promotion of seed germination (Bruns and Read 2000). As with these ericaceous, myco-heterotrophic plants, dormant seeds of remarkably small size often receive chemical stimulants from specific hosts or other biotic and/or abiotic chemical sources (Hauck et al 1992;Yoneyama et al 1998;Flematti et al 2004), while some plants awaiting dormancy breakage for seed germination in seed banks in the soil often require biological and/or physical decomposition of the seed coat (Warrag and Eltigani 2005;Baskin and Baskin 2004).…”
Section: Introductionmentioning
confidence: 99%